The Political Morality of School Composition: The Case of Religious Selection. Issue 2 (26th April 2021) - Clayton, Matthew; Mason, Andrew; Swift, Adam; Wareham, Ruth
Abstract : This article presents a normative framework for the assessment of education policies and applies it to the issue of schools' selecting their students on the basis of religious criteria. Such policies can be justified, and challenged, on many different grounds; public debate is not conducted in terms adequate to the task. The authors' main objectives are to supplement with non-consequentialist considerations a recent, consequentialist, approach to the normative assessment of education policy proposed by Brighouse et al. (2016, 2018), and to apply the proposed framework to issues of school composition and selection. They argue, further, that policies allowing schools to select all their students on the basis of their parents' religious affiliation cannot be justified.